Dever-poder geral de coerção nos processos de execução: a ADI 5941 e os limites da utilização das medidas atípicas estabelecidas no art. 139, IV com a finalidade de satisfação da obrigação de pagar - Botta, Flávia (2025)
Civil enforcement in Brazil faces challenges related to effectiveness, especially in monetary obligations, with controversy surrounding the atypical coercive measures set forth in Article 139, item IV, of the CPC/2015. The practical application of these measures raises questions regarding their limits, proportionality, and appropriateness, particularly in light of the ruling in ADI 5941. This study is justified by the high rate of unsuccessful enforcement actions in the judiciary and the need to understand the legislative innovations that expand the judge's powers, contributing to the balance between enforcement effectiveness and the fundamental rights of the defendant, a topic of great relevance for the improvement of civil procedural law. The general aim of this research is to investigate atypical coercive measures and analyze their practical and theoretical application in the context of monetary enforcement. The study examines the grounds for these measures, the limits set by the Supreme Federal Court (STF) in the ADI 5941 ruling, and possible guidelines for establishing legal doctrines in Repetitive Appeal 1137 at the Superior Court of Justice (STJ), proposing frameworks for their consistent and predictable application. Methodologically, a deductive model is adopted, with bibliographic and jurisprudential research. The chapters begin by addressing the problem of civil enforcement, the general theory of enforcement, the principles that govern it, such as effectiveness and good faith, and the atypical coercive measures, their limits and requirements, also analyzing the tensions between effectiveness and the protection of fundamental rights. The ADI 5941 and its affirmation of the constitutionality of Article 139, IV, of the Civil Procedure Code by the STF, as well as the possible guidelines to guide the judgment of Repetitive Appeal 1137 at the STJ, which delimit the practical application of these measures, are also discussed. The research concludes that, although atypical coercive measures represent a significant advancement in procedural effectiveness, their application requires an analysis of criteria related to the proportionality and necessity of the measures in relation to the procedural objective pursued, guided by the principles of efficiency and appropriateness, so as to avoid excesses in specific cases, ensure legal certainty, and respect the fundamental rights of the defendant, which is essential for the consolidation of a just and efficient enforcement system